Utilization of legume flours in wafer sheets. Issue 1 (22nd August 2019) - Tufan, Busra; Sahin, Serpil; Sumnu, Gulum
Abstract: In this study, it was aimed to analyze the impacts of replacement of 20% of wheat flour by lentil, chickpea, or bean flours on batter rheology as well as hardness, weight loss, sorption characteristics, and color of the wafer sheets. All formulations showed shear thinning behavior obeying power law. Lentil flour‐containing formula gave the highest flow behavior index and the lowest consistency coefficient value. Hardness of wafer sheets increased when legume flours were used. Increase in hardness value was less when chickpea flour was used as compared with the other legume flours. It was observed that upon baking, legume flour‐added samples had lower weight loss values. Usage of chickpea flour resulted in the lowest weight loss. Sorption results implied localized sorption indicating multilayer water molecules showing similar properties to liquid water. Wafers containing legume flours were not significantly different than the control wafer in terms of monolayer moisture content, K and C values of Gugenheim, Anderson and de Boer (GAB) model. The color of chickpea flour‐containing wafer was the closest to that of control sample. Overall, wafer sheets prepared by replacement of 20% wheat flour by chickpea flour was agreed to be the best in terms of the analyzed parameters.